Indicators of Fiscal Sustainability - Horne, Jocelyn (IMF Working Papers; Working Paper ;, 1991)
This paper assesses the usefulness of summary measures of fiscal sustainability for the purpose of multilateral surveillance. An overview of the main conceptual issues is first presented. Next, an assessment is made of the strengths and weaknesses of the summary measures in the context of their recent application to industrial countries by the OECD and the Fund. The measures are shown to highlight the inadequacy of using trends in public debt ratios to assess sustainability. However, the measures and their recent application are subject to a number of caveats, in particular in relation to their sensitivity to the discount rate, time paths of government expenditures and private sector behavior.